Formation processes of dislocation cells in cryorolled Zr upon annealing. (1st August 2013) - Shi, Y D; Guo, D F; Li, M; Zhang, Z B; Ma, T Y; Zhang, X Y
<x xml:space="preserve">Abstract</x> In the present study, the formation process of dislocation cells in cryorolled Zr has been studied. High density dislocations were introduced into pure Zr by employing cryorolling technique. Dislocation lamellas are yielded in cryorolled Zr at a high strain rate of <inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="mst-29-08-921-e01.tif"/> = 2·24 s−1, and these lamellas fragment or bend into dislocation cells during annealing processes. Instead, in the cryorolled Zr yielded at a low strain rate of <inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="mst-29-08-921-e02.tif"/> = 0·59 s−1, dislocation cells form by the fragmenting or the necking of dislocation tangle regions. The formation process of dislocation cells in cryorolled Zr is dependent on dislocation configurations induced in the metal.